(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Integration of Damage Differentials (IDD) method was developed in Faculty of Forest Industry. It is applicable e.g. for fatigue life computation of bandsaw blade. In this regard, stress oscillograms were presented. They vary about a comparatively great mean stress: in the order of the half of the maximum stress. An analogous case in bridge construction is considered in a Ph.D. thesis developed in Sofia University of Architecture, Civil Engineering and Geodesy where IDD was adopted. The great mean stress effect is clarified regarding how IDD takes it into account in contrast to standard methods in the civil engineering.